2019
DOI: 10.1177/1098300719876096
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Challenges in Adapting SWPBIS to a Dutch Context

Abstract: The transfer and adoption of school-wide approaches, like School-Wide Positive Behavior Interventions and Supports (SWPBIS), from one country to another, is an underexamined process. SWPBIS was mainly developed in the US. Although research shows that implementation of SWPBIS contributes to a positive school climate and a decrease in problem behavior, little is known about the generalizability of the effects in other countries. Of special interest is the role of underlying cultural values and concepts as reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
15
0
3
Order By: Relevance
“…In fact, this was the only item scoring at the same level as U.S. schools ( M = 1.49) whereas all other items scored lower (Kittelman et al, 2018). At the introduction of SWPBIS in the Netherlands, the systematic use of token economy systems met with resistance of teachers (Nelen et al, 2019). However, for most participating schools, this seemed to no longer be an issue as they clearly have managed to implement token economy systems according to requirements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, this was the only item scoring at the same level as U.S. schools ( M = 1.49) whereas all other items scored lower (Kittelman et al, 2018). At the introduction of SWPBIS in the Netherlands, the systematic use of token economy systems met with resistance of teachers (Nelen et al, 2019). However, for most participating schools, this seemed to no longer be an issue as they clearly have managed to implement token economy systems according to requirements.…”
Section: Discussionmentioning
confidence: 99%
“…When SWPBIS was introduced in the Netherlands, core features were formulated in a recognizable and culturally acceptable language, and procedures were adjusted to the Dutch educational context. Earlier research (Nelen, Willemse, Van Oudheusden, & Goei, 2019) in which Dutch SWPBIS experts were questioned about core features and procedures of SWPBIS in the Netherlands, showed that experts agreed on the importance of all core features and that cultural adaptation was merely about adjusting procedures. All adaptations seemed to be in line with the theoretical base of SWPBIS.…”
Section: Contextual Fitmentioning
confidence: 99%
See 2 more Smart Citations
“…The TFI was chosen because it is the most recently developed and up-to-date instrument, it is brief, and it is based on the factors and features in existing validated fidelity measures. The SET was chosen to compare TFI measurements with more objective data (Nelen, 2020b).…”
Section: Fidelity Of Implementationmentioning
confidence: 99%